Kiai's Strategy In Developing The Salafiyah Education System In The Middle Of Modernization - Muhammad Tahmid; Abu Darim (JOSSE: Journal of Social Science and Economics, 2022)
The Kiai's strategy has an important role in Islamic boarding schools to realize the goals and achieve a vision and mission of Islamic boarding schools. What is the kiai's strategy in developing the education system and what is the kiai's strategy in implementing the salafiyah education system in the midst of modernization. As well as knowing the nature, history, characteristics, education system, functions and goals in realizing this. There are two focuses of this research, namely: 1). What is the kiai's strategy in developing the salafiyah education system in the midst of modernization? 2). What is the kiai's strategy in implementing the salafiyah education system in the midst of modernization? 3). Why the Al-Yasini Integrated Islamic Boarding School must develop a salafiyah education system in the midst of modernization. In this study, the author uses a type of qualitative research with a qualitative descriptive approach. Data collected through observation, interviews and documentation. The validity of the data by means of triangulation. The results of the research found at the research site indicate that the kiai's strategy in developing the Salafiyah pesantren education system in the midst of modernization (a case study at PP Terpadu Al-Yasini Pasuruan) is going well. The policy carried out by the kiai is to require participation in all formal and non-formal activities.